2021
DOI: 10.3390/mi12020210
|View full text |Cite
|
Sign up to set email alerts
|

Poly(N-isopropylacrylamide) Hydrogel for Diving/Surfacing Device

Abstract: Underwater robots and vehicles have received great attention due to their potential applications in remote sensing and search and rescue. A challenge for micro aquatic robots is the lack of small motors needed for three-dimensional locomotion in water. Here, we show a simple diving and surfacing device fabricated from thermo-sensitive poly(N-isopropylacrylamide) or a poly(N-isopropylacrylamide)-containing hydrogel. The poly(N-isopropylacrylamide)-containing device exhibited fast and reversible diving/surfacing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The interaction between the amide groups becomes more intense and tends to form an eight-membered ring structure . The PNIPAM chain collapses, exposing the hydrophobic isopropyl groups and the hydrophilicity and density of PNIPAM gel decrease, which tends to distribute on the oil–water interface …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between the amide groups becomes more intense and tends to form an eight-membered ring structure . The PNIPAM chain collapses, exposing the hydrophobic isopropyl groups and the hydrophilicity and density of PNIPAM gel decrease, which tends to distribute on the oil–water interface …”
Section: Results and Discussionmentioning
confidence: 99%
“…To visually reflect the process of the co-polymer nano− microspheres moving from the water phase to the water−oil interface during being heated, we place the gel in water at 25 °C and observe the rising process of the gel accompanied by increasing the temperature (Figure 4c). 37 When the temperature exceeds 32 °C, the gel (H3) starts to float up and slowly reaches the water surface as the temperature increases. By contrast, the pure PAM sample (H0) does not move to the oil−water interface.…”
Section: Ift Analysismentioning
confidence: 99%
“…This PDF file includes: Supplementary Text Fig. S1 to S15 Table S1 to S4 References (45)(46)(47)(48)(49)(50)(51) Other Supplementary Material for this manuscript includes the following: Movie S1 to S6 Funding: Research reported in this publication was supported by the NSF (EFMA-1830893). We thank R. Schulman for discussions.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…However, hydrogels can still be applied to underwater robots to provide some auxiliary functions, such as stealth, buoyancy control, and so on. [119,120]…”
Section: Responsive Hydrogel Actuationmentioning
confidence: 99%